Enzalutamide and CXCR7 inhibitor combination treatment suppresses cell growth and angiogenic signaling in castration‐resistant prostate cancer models. Issue 10 (30th January 2018) - Luo, Yong; Azad, Abul Kalam; Karanika, Styliani; Basourakos, Spyridon P.; Zuo, Xuemei; Wang, Jianxiang; Yang, Luan; Yang, Guang; Korentzelos, Dimitrios; Yin, Jianhua; Park, Sanghee; Zhang, Penglie; et al.
Abstract : Previous studies have shown that increased levels of chemokine receptor CXCR7 are associated with the increased invasiveness of prostate cancer cells. We now show that CXCR7 expression is upregulated in VCaP and C4‐2B cells after enzalutamide (ENZ) treatment. ENZ treatment induced apoptosis (sub‐G1) in VCaP and C4‐2B cells, and this effect was further increased after combination treatment with ENZ and CCX771, a specific CXCR7 inhibitor. The levels of p‐EGFR (Y1068), p‐AKT (T308) and VEGFR2 were reduced after ENZ and CCX771 combination treatment compared to single agent treatment. In addition, significantly greater reductions in migration were shown after combination treatment compared to those of single agents or vehicle controls, and importantly, similar reductions in the levels of secreted VEGF were also demonstrated. Orthotopic VCaP xenograft growth and subcutaneous MDA133‐4 patient‐derived xenograft (PDX) tumor growth was reduced by single agent treatment, but significantly greater suppression was observed in the combination treatment group. Although overall microvessel densities in the tumor tissues were not different among the different treatment groups, a significant reduction in large blood vessels (>100 μm 2 ) was observed in tumors following combination treatment. Apoptotic indices in tumor tissues were significantly increased following combination treatment compared with vehicle control‐treated tumor tissues. Our results demonstrate that significant tumor suppression mediated by ENZ and CXCR7 combination treatment may be due, in part, to reductions in proangiogenic signaling and in the formation of large blood vessels in prostate cancer tumors. Abstract : What's new? Despite promising initial responses to androgen deprivation therapy, advanced prostate cancer eventually progresses to metastatic castration‐resistant disease in the majority of men. This increased aggressiveness in tumor behavior is associated with elevated expression of chemokine receptor CXCR7. Here, in VCaP and C4‐2B prostate cancer cell lines, combined treatment with the androgen receptor signaling inhibitor enzalutamide (ENZ) and the CXCR7 inhibitor CCX771 was found to enhance apoptosis and suppress cell motility, invasion and proangiogenic signaling. Experiments in orthotopic VCaP xenograft and subcutaneous MDA133‐4 patient‐derived xenograft models corroborated observations in cells and demonstrated significant reductions in blood vessel formation.